2020
DOI: 10.1016/j.annonc.2020.08.954
|View full text |Cite
|
Sign up to set email alerts
|

815MO The impact of chemosensitivity assessed by modeled CA-125 KELIM on the likelihood of long progression-free survivorship (PS) after 1st line treatment in ovarian cancer: An analysis of 4,450 patients

Abstract: subgroups, including by presence of genome-wide loss of heterozygosity, will be presented. Table: 814MO Non-gBRCAm PSR OC Doublet cohort (O+D) n[32 Triplet cohort (O+D+B) n[31 24-w DCR, % 28.1% (90% CI 15.5e43.9) 77.4% (90% CI 61.7e88.9) Confirmed ORR, % 31.3% (95% CI 16.1e50.0) 77.4% (95% CI 58.9e90.4) Median confirmed DOR (mo)6.9 (IQR 5.7e11.1) 11.1 (IQR 9.0e16.4)Median PFS (mo) 5.5 (95% CI 3.6e7.5) 14.7 (95% CI 10.0e18.1) CI, confidence interval; IQR, interquartile range.Conclusions: Combining O+D and O+D+B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Of note, KELIM was shown to be more accurate than the CA-125 Gynecology Cancer In-terGroup response criterion for characterizing chemotherapy efficacy in the first-line setting. 15,17,[19][20][21] Veliparib is an oral PARPi that inhibits poly (adenosine diphosphate-ribose) polymerase (PARP) activity without substantial trapping of PARP onto DNA damage repair intermediates, 22,23 thereby making veliparib more suitable for administration in combination with platinum-based chemotherapy. 24 The efficacy of veliparib was assessed in combination with standard frontline platinum-based chemotherapy (concomitant-veliparib arm; dose reduced during combination therapy) or in the same regimen followed by veliparib continued as a monotherapy in the maintenance phase (veliparib-throughout arm) in the VELIA phase III trial.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, KELIM was shown to be more accurate than the CA-125 Gynecology Cancer In-terGroup response criterion for characterizing chemotherapy efficacy in the first-line setting. 15,17,[19][20][21] Veliparib is an oral PARPi that inhibits poly (adenosine diphosphate-ribose) polymerase (PARP) activity without substantial trapping of PARP onto DNA damage repair intermediates, 22,23 thereby making veliparib more suitable for administration in combination with platinum-based chemotherapy. 24 The efficacy of veliparib was assessed in combination with standard frontline platinum-based chemotherapy (concomitant-veliparib arm; dose reduced during combination therapy) or in the same regimen followed by veliparib continued as a monotherapy in the maintenance phase (veliparib-throughout arm) in the VELIA phase III trial.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses also showed that their respective impacts were different according to the chemosensitivity. Indeed, the benefit offered by complete IDS relative to the risk of subsequent platinum-resistant relapse, and survival, was maximum in patients with poorly chemosensitive diseases, in contrast to patients with highly chemosensitive diseases, whose prognostic was mainly driven by the chemosensitivity [54,58,59]. For example, Fig.…”
Section: Respective Roles Of the Surgery And Of The Tumor Primary Chemosensitivitymentioning
confidence: 99%
“…These studies have confirmed the capacity of KELIM to reproducibly predict: (1) the likelihood of complete resection at IDS in the neoadjuvant setting [54,55,57], (2) the probability of subsequent platinum-resistant relapse [54,58], (3) the patient PFS and OS (Fig. 1 showing hazard-ratios for PFS and OS in patients having favorable or unfavorable KELIM)) [51,[53][54][55]57], and 4) the probability of complete remission >5 years after first-line treatment (OR, 4.24, 95 %CI 2.36-7.69) [59]. These data confirmed that the longitudinal kinetics of CA-125 during the first 3 cycles of chemotherapy, captured by KELIM, is the reflection of an intrinsic property of the tumor cells related to the sensitivity to chemotherapy independently on the received regimen.…”
Section: Indicators Of Tumor Primary Chemosensitivitymentioning
confidence: 99%
“…In a pooled analysis of datasets presented above, the prognostic value of KELIM regarding the probability of long-term complete remission (LCR) was assessed after first-line treatment [ 3 ]. LCR was defined as complete remission >5 years after initial treatment.…”
Section: Kelim: An Early Marker Of the Tumor Primary Chemosensitivity In Ovarian Cancer In First-line Settingmentioning
confidence: 99%
“…Due to an initially asymptomatic disease, approximately 75% of patients at the time of diagnosis present with advanced tumors (FIGO stages III to IV) known to have a poor prognosis [ 2 ]. Despite standard treatment associating debulking surgery and platinum-based chemotherapy, recurrent disease develops in more than 95% of patients within 5 years [ 3 ]. Relapse is typically incurable, with most patients receiving multiple additional lines of treatment before ultimately dying from the disease.…”
Section: Introductionmentioning
confidence: 99%